PENGEMBANGAN MEDIA VIDEO PRAKTIKUM MENGGUNAKAN APLIKASI CANVA PADA MATA KULIAH FISIOLOGI TUMBUHAN UNTUK MAHASISWA PENDIDIKAN BIOLOGI SEMESTER V FKIP UNIVERSITAS PASIR PENGARAIAN - Meirina Brahmana, Eti; Febriani; Mubarrak, Jismi; Lestari, Rena; Dahlia, Dahlia (Fakultas Keguruan dan Ilmu Pendidikan Universitas Pasir Pengaraian, 2024)
This study aims to determine the feasibility of plant physiology practicum video media for fifth semester biology students at FKIP of University of Pasir Pengaraian . This research was carried out from March to July 2023. The type of research used was the Brog and Gall Research and Development model. The population in this study were fifth semester students of the Biology Education Study Program class of 2021. Data was collected using a questionnaire and data were analyzed descriptively. The results showed that the plant physiology practicum video media for biology students in semester V as a whole was declared